Účinnost a snášenlivost tafluprostu 0,0015% bez konzervačních látek v léčbě glaukomu a oční hypertenze - Karhanová, M; Mlčák, P; Fryšák, Z; Marešová, K (Ceska a slovenska oftalmologie, 2012)
AIM: The aim of the study was to evaluate the efficacy, safety and local tolerability of preservative-free tafluprost 0.0015% (Taflotan®) in patients with glaucoma and ocular hypertension. MATERIALS AND METHODS: Multicentric, prospective observation study was performed in the Czech Republic from October 2010 to April 2011. A total of 78 centers participated and 754 patients were included. After the doctors decision to start the treatment with Taflotan®, the patients demographic data, previous treatment, intraocular pressure and the reason for switching the medication were recorded. At the follow-up visit after 6-12 weeks, the intraocular pressure, local tolerability (a 5-level scale), the patients and doctors satisfaction (a 4-level scale), and the patients preference were recorded. RESULTS: Altogether, data of 496 patients were evaluated. The majority of them were women (64.9 %). The patients mean age was 58.5 years. The most common diagnosis was primary open angle glaucoma (79.2 %), followed by ocular hypertension (7.3 %), normal tension glaucoma (4.2 %), and pseudoexfoliation glaucoma (3.6 %). In 140 patients, tafluprost 0.0015% was the first antiglaucomatous medication started, 261 patients switched from another monotherapy, and 95 patients were treated with fixed- or nonfixed combinations before starting tafluprost 0.0015%. The most common reason for switching to Taflotan® was local intolerability to the current antiglaucomatous therapy (most often irritation of the eye and hyperemia). The intraocular pressure decreased significantly from 19.9 ± 4.5 mm Hg to 16.3 ± 3.0 mm Hg (p < 0.001). The subjective tolerability of the antiglaucomatous therapy improved rapidly, with 57.4 % of patients rating the tolerability of Taflotan® as "very good" and 34.5 % as "good". In addition, 94.4 % of patients and 96.0 % of ophthalmologists were "very satisfied" or "satisfied" with the treatment. At the final visit, 79.8 % of patients preferred Taflotan® to the previous treatment. CONCLUSION: Taflotan® significantly decreased the intraocular pressure. It was well tolerated even in patients with previous intolerability to another antiglaucomatous therapy, including prostaglandins. The patients and ophthalmologists satisfaction with Taflotan® was high.
Keywords: oční hypertenze; glaukom; Humans; lidé středního věku; dítě; Child; Female; Aged; mladý dospělý; dospělí; Glaucoma; senioři; lidé; nitrooční tlak; Adult; ženské pohlaví; Male; prostaglandiny syntetické; Middle Aged; Adolescent; Young Adult; Prostaglandins, Synthetic; Ocular Hypertension; mužské pohlaví; Prostaglandins F; prostaglandiny F; Intraocular Pressure; mladiství